Examination of soil parameters based on the evaluation of the spectroradiometric reflectance characteristics of the topsoil - Bakos, Károly; Dobos, Attila; Nagy, János (Acta Agraria Debreceniensis, 2014)
In this article we are presenting the methodology applied to analyse and interpret the topsoil surface reflectance parameters of multiple samples collected in the Mugello valley area in northern Italy in October 2012. The main aim of the whole project was to discover geomorphological behaviour and situation of the area ino order to improve potential for correct dating of certain archaeological artefacts found in the nearby areas. One of the crucial problem researchers are facing in the area is the lack of understanding of the underlying geological and geomorphological processes that were describing and characterizing the area and that played important role not only in the current geography and landscape formation but also in the transportation of various sediments and artefacts. In this particular research the main aim is to examine the possibility of developing a quick way to assess low level properties of the soil using hand held spectrometer and rapid analysis of cross-section using in situ measurement techniques. In this work we collected over 2000 individual samples of topsoil surface reflectance properties that we organized into a spectral library. This library is then to be used to describe physical and chemical processes in the soil. To support the analysis results were compared to analysis results from different kind of assessments in the same area. Our results show a great potential of application of hand held imaging spectrometer in soil property analysis based on the top soil surface reflectance parameters.